Application of methods of system analysis for modeling the process of distance learning - S. Ya. Zhukovich (Системный анализ и прикладная информатика, 2021)
A mathematical model of distance learning based on control theory in the form of an inhomogeneous linear differential equation is proposed. On the basis of the coefficients of assimilation and forgetting, determined with the help of special tests, it is possible to predict, in some approximation, the level of current knowledge of both the individual trainee and the group or stream of students.